PENGEMBANGAN BAHAN AJAR MENULIS PETUNJUK BERBASIS MODEL PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR MP PKB DI KELAS IV SEKOLAH DASAR - Refiarni Refiarni (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2018)
Based on test validity, data showed that the average percentage of RPP obtained 88,6% of the validator experts with very valid category, from 90.8% validator practitioners were categorized as very valid. The results of the average percentage of teaching materials obtained 93,05% of the validator experts with very valid category, from the validator practitioner was 92.24% categorized as very valid. The test results practicalities of materialize RPP with a percentage of 88.6% to the category of very practical. Rate response obtained 90,0% of teachers and learners responses votes 99.98%. The effectiveness of the learning device seen from the activity of 89,10% was obtained with very good category. From the assessment process of writing the instructions obtained 92.40% with a very high category. From the results of the assessment wrote directions in mind that the percentage of completeness result of write instructions are likely to increase. Thus, learning to write the instructions based learning model MP PKB increase thinking skills help students understand the stages of the writing process instructions. Based on these results, it was concluded that the teaching material to write the instructions based learning model increased ability to think for fourth grade students developed can be considered valid, practical, and effective.